2006
DOI: 10.1161/01.atv.0000209998.73303.b5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Angiotensin II–Activated Human LOX-1 Promoter

Abstract: Objective-LOX-1, a receptor for oxidized low-density lipoprotein, plays a critical role in atherosclerosis. Its expression is upregulated by pro-atherogenic stimuli, such as angiotensin II (Ang II). In this study, we explored LOX-1 transcriptional promoter activation in response to Ang II in human coronary artery endothelial cells (HCAECs). Methods and Results-We constructed full-length and deletion LOX-1 promoter mutants and examined their activation in response to Ang II in HCAECs. The Ang II (1 mol/L for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…In keeping with previous in vitro studies, 2 Ang II infusion enhanced LOX-1 expression in the wild-type mice ( Figure 5D). As expected, LOX-1 was not detectable in LOX-1 KO mice hearts.…”
Section: Oxidative Stress Induced By Ang II and Norepinephrine And Thsupporting
confidence: 92%
See 3 more Smart Citations
“…In keeping with previous in vitro studies, 2 Ang II infusion enhanced LOX-1 expression in the wild-type mice ( Figure 5D). As expected, LOX-1 was not detectable in LOX-1 KO mice hearts.…”
Section: Oxidative Stress Induced By Ang II and Norepinephrine And Thsupporting
confidence: 92%
“…5,6 Although LOX-1 mRNA expression is minimal in normal arterial tissues, it is markedly upregulated in vascular tissues of spontaneously hypertensive animals, suggesting a correlation between LOX-1 and hypertension. 7 This concept is supported by in vitro observations that Ang II upregulates LOX-1 expression, 2 and angiotensin-converting enzyme inhibitors and AT1R blockers decrease LOX-1 expression. 8 These findings suggest that LOX-1 overexpression may contribute to the pathological states induced by Ang II.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies showed that statins (eg, simvastatin) significantly reduced the MCP-1 level in monocytes in vitro [12] . In addition, angiotensin II receptor blockers (eg, irbesartan) can also decrease the expression of MCP-1 and relieve the extent of atherosclerotic plaques [22,23] . However, less synergistic effects on the expression of MCP-1 were observed by the combination of statins and ARB.…”
Section: Discussionmentioning
confidence: 99%